Tiến tới thiết lập một hệ thống độ cao quốc gia có nhiều điểm gốc và thống nhất cho cả lãnh thổ và lãnh hải ở nước ta - Lân, Phạm Hoàng (Vietnam Journal of Earth Sciences, 2008)
Towards to establishing a national height system with multi-initial and unified points for both terrestrial and sea territories in our country